Study and Analysis on Differernt Flow Arrangements Using Different Fluids in Micro Channel Heat Sink for High Performance - Kumar, Neeraj; Singh, Nirmal Kant; Garg, Harry (Asian Journal of Engineering and Applied Technology, 2014)
The high performance of the micro channel depends upon the number of parameters like geometrical & flow parameters. In this paper a flow analysis of the different arrangements of the fluid entrance for micro channel based heat sink has been carried out. The fluid can enter in the different ways like upper flow, front flow and side flow. The arrangement is important because the formation of the boundary layers will be affected based on the flow arrangements. The fluid after entering goes into the plenum & based upon these arrangements there is a fl ow variation. Ultimately the performance of the liquid through the channel varies here we investigate the best flow arrangement for the high performance of micro channel heat sink that is independent of the scaling. Fluid flow and heat transfer are investigated on the basis of the simulation.